1999
DOI: 10.1034/j.1398-9995.1999.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in asthma: an updated systematic review

Abstract: including oral, sublingual, and inhaled immunotherapy.Recombinant peptides containing the relevant epitopes, but lacking the ability to cross-link IgE bound to mast cells, have been evaluated in clinical trials. Finally, the Cochrane Collaboration has standardized protocols for systematic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 137 publications
(143 reference statements)
1
66
1
12
Order By: Relevance
“…At the end of the experiment, mice were killed by cervical dislocation, spleens were removed and single cell suspensions were prepared by teasing the tissue apart. Erythrocytes were lysed by incubating the cells for 1 min in lysis buffer (155 mm NH 4 Cl, 10 mm KHCO 3 , 100 m EDTA-disodium, pH 7.4). After extensive washing splenocytes were passed through a 100-m cell strainer (Becton Dickinson Labware, Franklin Lakes, NJ, USA) to remove cell debris and were subsequently analyzed for cytokine production.…”
Section: Mice and Immunization Protocol For Induction Of Ige Ab Produmentioning
confidence: 99%
“…At the end of the experiment, mice were killed by cervical dislocation, spleens were removed and single cell suspensions were prepared by teasing the tissue apart. Erythrocytes were lysed by incubating the cells for 1 min in lysis buffer (155 mm NH 4 Cl, 10 mm KHCO 3 , 100 m EDTA-disodium, pH 7.4). After extensive washing splenocytes were passed through a 100-m cell strainer (Becton Dickinson Labware, Franklin Lakes, NJ, USA) to remove cell debris and were subsequently analyzed for cytokine production.…”
Section: Mice and Immunization Protocol For Induction Of Ige Ab Produmentioning
confidence: 99%
“…[17][18][19] A recent Cochrane metaanalysis assessed allergen specific immunotherapy for asthma. 20 Eighty-eight clinical trials fulfilled the criteria for inclusion.…”
Section: Subcutaneous Immunotherapy (Scit)mentioning
confidence: 99%
“…A meta-analysis of all trials published between 1954 and 1998 found clear evidence for the beneficial effects of SIT in asthma. 19 Symptom scores were reported in 22 trials and overall there was a small but definite improvement in those groups treated with mite SIT or pollen SIT, compared to the placebo-treated groups. There was a parallel reduction in asthma medication usage but no improvement in lung function measurements.…”
Section: Sit For Asthmamentioning
confidence: 99%
“…Concern over adverse reactions, including a small number of fatalities, has led some countries to restrict the use of SIT for asthma treatment, although asthma remains a common indication for SIT in many parts of North America and continental Europe. 18,19 Current drug therapies for asthma suppress airway inflammation and relieve bronchospasm. None of these treatments are curative and asthma recurs rapidly on ceasing treatment.…”
Section: Sit For Asthmamentioning
confidence: 99%